2011
DOI: 10.1007/s13213-011-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence assays and slime production of Staphylococcus aureus strains after their incubation in seawater microcosms

Abstract: In this study, we incubated four strains of Staphylococcus aureus for 8 months in seawater microcosms. The biofilm formation on microplates and on glass and the surface hydrophobicity of starved cells were investigated. Our results showed that the stressed cells increased their hydrophobicity from 12 to 44% and also their capacity for producing biofilm. Indeed, after 8 months of incubation in seawater microcosms, all strains became slime positive on CRA plates and very adherent to polystyrene microplates or gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Among the S. epidermidis was a slime-producer developing almost black colonies on CRA plates ( Figure 6). Indeed, slime production play an important role in the pathogenesis of infections caused by different micro-organismes (Bekir et al, 2010) and is considered to be a significant virulence factor for some staphylococci (Bekir et al, 2011) as well as for Aeromonas spp which indicates the high-risk source contamination (Sechi et al, 2002). Slimes are generally polysaccharidic materials, although other poly- mers may also be present.…”
Section: Resultsmentioning
confidence: 99%
“…Among the S. epidermidis was a slime-producer developing almost black colonies on CRA plates ( Figure 6). Indeed, slime production play an important role in the pathogenesis of infections caused by different micro-organismes (Bekir et al, 2010) and is considered to be a significant virulence factor for some staphylococci (Bekir et al, 2011) as well as for Aeromonas spp which indicates the high-risk source contamination (Sechi et al, 2002). Slimes are generally polysaccharidic materials, although other poly- mers may also be present.…”
Section: Resultsmentioning
confidence: 99%
“…They were visualized under ultraviolet transillumination, and photographed using Gel Doc XR apparatus (Biorad, USA) (Bekir et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The used primers were specific to Sa442 gene (5′-CGTAATGAGATTTCAGTAGATAATACAACA-3′ and 5′-AATCTTTGTCGGTACACGATATTCTTCACG-3′) (Murdoch et al 2004;Bekir et al 2011). The PCR was performed using the following thermal cycles: an initial denaturation step at 94°C for 5 min followed by 35 cycles (94°C for 90 s, 57°C for 30 s, and 72°C for 90 s), followed by a final extension step at 72°C for 10 min.…”
Section: Pcr Confirmation Of S Aureus Strainmentioning
confidence: 99%
“…This behavior can be attributed to the conservation of surface antigen integrity in stressed S. aureus. According to Bekir et al (2011), stress induces the reduction of the cell size, the increase in cell number, the lost of small granules and inclusion bodies, the lost of the distinct three-layered integrity of the outer membrane, peptidoglycan, and the inner membrane to retain only remnants of those structures, the compression of the nuclear region into the cell center surrounded by a denser cytoplasm, and the formation of extended or convoluted structures from the cell wall which are pulled away from the cell membrane. In previous work, it was shown that stress phenomenon can lead to the alteration of the S. bovismorbificans envelope (Bakhrouf et al 2008).…”
Section: Detection Of Bacteria Cells Using Electrochemical Impedance mentioning
confidence: 99%